Increased expression of putative cancer stem cell markers in the bone marrow of prostate cancer patients is associated with bone metastasis progression. Issue 16 (21st September 2013) - Ricci, Estelle; Mattei, Eve; Dumontet, Charles; Eaton, Colby L.; Hamdy, Freddy; van der Pluije, Gabri; Cecchini, Marco; Thalmann, George; Clezardin, Philippe; Colombel, Marc
<x xml:space="preserve">Abstract</x> BACKGROUND The number of cells positive for the α‐6 and α‐2 integrin subunits and the c‐Met receptor in primary tumors and bone biopsies from prostate cancer patients has been correlated with metastasis and disease progression. The objective of this study was to quantify disseminated tumour cells present in bone marrow in prostate cancer patients using specific markers and determine their correlation with metastasis and survival. METHODS Patients were included at different stage of prostate cancer disease, from localised to metastatic castration‐resistant prostate cancer. Healthy men were used as a control group. Bone marrow samples were collected and nucleated cells separated. These were stained for CD45, α‐2, α‐6 integrin subunits and c‐Met and samples were processed for analysis and quantification of CD45‐/α2+/α6+/c‐met + cells using flow cytometry. Clinical and pathological parameters were assessed and survival measured. Statistical analyses were made of associations between disease specific parameters, bone marrow flow cytometry data, prostate‐specific antigen (PSA) progression free survival and bone metastases progression free survival. RESULTS For all markers, the presence of more than 0.1% positive cells in bone marrow aspirates was significantly associated with the risk of biochemical progression, the risk of developing metastasis and death from prostate cancer. CONCLUSIONS Quantification of cells carrying putative stem cell markers in bone marrow is a potential indicator of disease progression. Functional studies on isolated cells are needed to show more specifically their property for metastatic spread in prostate cancer. Prostate 73:1738–1746, 2013. © 2013 Wiley Periodicals, Inc.